2015
DOI: 10.1039/c5ra03580e
|View full text |Cite
|
Sign up to set email alerts
|

Water steam effect during high CO2 chemisorption in lithium cuprate (Li2CuO2) at moderate temperatures: experimental and theoretical evidence

Abstract: Li2CuO2 is able to chemisorb high quantities of CO2 in the presence of water steam at low temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 63 publications
2
49
0
Order By: Relevance
“…The N 2 adsorption-desorption results showed type-II isotherms according to the IUPAC classication, 38 without any kind of hysteresis loop. 19 For comparison purposes, Fig. These results provide evidence of densication, which should be attributed to both the carbonation and moderate pressure effects.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The N 2 adsorption-desorption results showed type-II isotherms according to the IUPAC classication, 38 without any kind of hysteresis loop. 19 For comparison purposes, Fig. These results provide evidence of densication, which should be attributed to both the carbonation and moderate pressure effects.…”
Section: Resultsmentioning
confidence: 92%
“…In a previous paper, 19 it was already shown that Li 2 CuO 2 is able to trap CO 2 chemically at low temperatures in the presence of water vapor, where H 2 O works as a supercial catalytic intermediate, decreasing the activation energy of the CO 2 chemisorption process. Therefore, the ball-milled Li 2 CuO 2 , possessing a larger surface area, is expected to present an interesting CO 2 capture process in the Li 2 CuO 2 -CO 2 -H 2 O system at low temperatures (30 to 80 C).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…According to those studies, sodium cobaltate and metal‐containing phases are not able to chemisorb CO 2 at low temperatures ( T < 150 °C) in dry conditions. As previously mentioned, water vapor improves CO 2 capture on different alkaline ceramics at low temperatures . Therefore, addition of water vapor may enhance CO 2 chemisorption capacity on NaCoO 2 at such a low‐temperature range.…”
Section: Introductionmentioning
confidence: 76%
“…In these materials, CO 2 capture at the low‐temperature range and in dry conditions is usually poor, achieving improvements only when the particle surface area is highly increased or when their chemical surface is modified . Nevertheless, it has been reported that these ceramics are able to trap more CO 2 at low temperatures in the presence of water vapor . The alkaline ceramics that have been studied under these conditions are Li 2 ZrO 3 , Na 2 ZrO 3 , Li 5 AlO 4 , CaO, Li 4 SiO 4 , Na 2 SiO 3, and more recently Li 8 SiO 6 and Li 2 CuO 2 .…”
Section: Introductionmentioning
confidence: 99%